Systematic Literature Review: Analisis Kemampuan Representasi Matematis Siswa Terhadap Gaya Belajar - Icha putri; Rhomiy Handican; Rilla Gina Gunawan (Griya Journal of Mathematics Education and Application, 2022)
This study aims to conduct a literature review related to the ability of students' mathematical representation of learning styles. The method used in this research is SLR (Systematic Literature Review). Data collection is done by identifying or reviewing all articles that have the same research topic in this study. The articles used in this study were 20 journal articles obtained by the Google Scholar database using the Harzing's Publish or Perish application. The results of this study revealed that the students' mathematical representation ability on learning styles obtained information that found forms of learning styles in the articles collected that focused on learning abilities, learning styles, and their representation. Which in this case only takes on visual, auditory, and kinesthetic learning styles. The results of this study are expected to be beneficial for learning and be used as examples of the use of various mathematical concepts around us.